Validation of Anti-Hiv 1/2 Confirmatory Immunoblot Assay and Development of Algorithm For Anti-Hiv Testing At A Specialized Healthcare Facility In Pakistan - Raza, Ali; Noor Fatima Shahid; Muhammad Numan; Anam Yousaf (Pakistan Armed Forces Medical Journal, 2026)
Objective: To validate the Anti-HIV 1/2 confirmatory, immunoblot assay and develop an optimized diagnostic algorithm and enhance Human Immunodeficiency Virus (HIV) detection by integrating serological and molecular methods. Study Design: Cross-sectional analytical study. Place and Duration of Study: Pakistan Kidney and Liver Institute and Research Center (PKLI&RC), Lahore, Pakistan, from Feb to Jul 2024. Methodology: This study evaluated the diagnostic performance of the Anti-HIV 1/2 immunoblot assay and proposed a multi-step algorithm for HIV detection. Participants included hospitalized patients and blood donors. Initial screening were confirmed using Elecsys® HIV Combi PT assay through Electrochemiluminescence Immunoassay (ECLIA). Reactive samples were confirmed using the Bio-Rad Geenius™ HIV 1/2 confirmatory assay and Nucleic Acid Testing (NAT). Additional testing was performed using the Bioline™ HIV Immunochromatographic Test (ICT). Results: Sixty participants were enrolled. Both immunoblot and ICT assays exhibited 100.00% sensitivity and specificity. NAT Polymerase Chain Reaction (PCR) demonstrated 100.00% sensitivity and 92.30% specificity, detecting acute infections missed by serological tests. Conclusion: Integrating serological and molecular diagnostic improves HIV detection accuracy. The proposed algorithm, including ECLIA, immunoblot, and NAT, proved reliable. Modifying the ECLIA cutoff to ≥ 75.215 improved specificity from 57.70% to 100.00% while maintaining 100.00% sensitivity.